Experimental Pathological Study of Nitrate Toxicity in Broilers - Al-saadi, Raghad N.; Al-Sultan, Imad I. (The Iraqi Journal of Veterinary Medicine, 2004)
This study was aimed to understand the chronic pathological change which is produced after potassium nitrate intake via water and food to broiler chicks for six weeks and in different concentrations also after stoppage for four weeks of nitrate intake. 135 chicks one day old fabrow breed were used, after two weeks aclimazation, chicks separated in to seven groups, one was control and the other six were given potassium nitrate in drinking water or in food in concentration 0.25, 0.5, 0.75 gm/kg of the body weight to each group. Gross and histopathological changes were studied, the pathological alteration characterized by gastritis of true stomach with metaplasia of gastric mucosa and chronic enteritis. Hepatic cell degeneration and necrosis .kidney showed congestion, haemorrhage and nephrosis. The thyroid gland was atrophied and the spleen was active due to hyperplasia of lymphoid cells and germinal centers. There was increase in the size of the lung which showed microscopically interstitial pneumonia, the brain was grossly soft and congested and microscopically there was degeneration of purkinge cell and increase neuromicroglial cells infiltration.